Changes in antiepileptic drug prescriptions over a decade in childbearing women in Lombardy region, Italy. Issue 3 (13th September 2021) - Clavenna, Antonio; Campi, Rita; Putignano, Daria; Fortino, Ida; Bonati, Maurizio
Abstract : Aims: To describe the antiepileptic drug (AED) prescription pattern in pregnant women and women of childbearing age in the 2010–2019 period in the Lombardy region, Italy. Methods: The Lombardy region administrative healthcare databases (2010–2019) were analysed. AEDs were classified as drugs belonging to the N03A subgroup of the Anatomical Therapeutic Chemical Classification System. Women aged 15–49 years were considered as being of childbearing age, while exposure during pregnancy was estimated taking into account the 12 months before delivery (International Classification of Diseases, Ninth Revision, Clinical Modification, ICD‐9‐CM codes in the diagnosis record from 650 to 659). Results: During 2019, 16 605 women of childbearing age (prevalence: 14.8‰) received at least 1 AED prescription. Pregabalin was the most widely used antiepileptic in women of childbearing age (22.3%), followed by valproic acid (20.0%). In 2010, the prevalence of valproic acid prescription to women of childbearing age was 30.2%; in 2019 this was 20.0%. In pregnant women, this prevalence was 24.9% in 2010 and 14.1% in 2019. Starting from 2017, levetiracetam and lamotrigine were the most commonly drugs prescribed to pregnant women. Conclusion: Despite the decrease in valproic acid prescription over time, this drug is still among the most used AEDs, in particular in women of childbearing age. Educational interventions for healthcare professionals and women are needed in order to reduce the risk of unplanned pregnancy.